2000
DOI: 10.1007/bf01300350
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of protection by latex gloves during orthodontic therapy

Abstract: The wearing of gloves during orthodontic or dental treatment is generally indicated for reasons of hygiene and protection against infection. This study was aimed at determining the extent and localization of perforations caused by the various orthodontic treatment techniques and interrupting the infection barrier. The impermeability was tested by means of a water retention test according to European standard EN 455, Part 1, performed on 1600 Centramed (Centramed, Koblenz), Tekmedic and SafeEx non-sterile dispo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
4
0
5
Order By: Relevance
“…Likewise, preventing bacterial contamination of the canal system should also be beneficial in achieving successful treatment outcomes. It has been suggested that the external surfaces of examination gloves are a possible source for microbial contamination (10). This study showed that examination gloves straight out of the box are relatively free of bacteria, whether from the beginning or end of the box.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Likewise, preventing bacterial contamination of the canal system should also be beneficial in achieving successful treatment outcomes. It has been suggested that the external surfaces of examination gloves are a possible source for microbial contamination (10). This study showed that examination gloves straight out of the box are relatively free of bacteria, whether from the beginning or end of the box.…”
Section: Discussionmentioning
confidence: 64%
“…Although use of gloves in the dental field is primarily for the benefit of the healthcare worker for infection prevention and hygiene (8,9), little information is available regarding microbial contamination of gloves before and during use. Nonsterile latex gloves have been shown to have high numbers of cultivable bacteria after use in clinical dentistry (10). Furthermore, Olsen et al showed that examination gloves tested positive for gram negative rods or enterococci after contact with patients' oral mucous membranes 64% of the time, thus being a potential source for microbial contamination of the operative field (11).…”
mentioning
confidence: 99%
“…This specimen location was chosen to be compatible with the large area needed for the viral penetration tests. Also, others have found the dorsum/palm areas to be sites with significant numbers of perforations and pinholes during orthodontic procedures and lung surgery 22, 23…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, others have found the palm/dorsal area to be sites with significant numbers of perforations and pinholes during orthodontic procedures and lung surgery. 17,18 Specimens used for both the flex-fatigue and viral challenge tests were rinsed in deionized water to remove powder and surface debris before testing.…”
Section: Methodsmentioning
confidence: 99%